Α-Tocopherol Stereoisomer Profiles in Matched Human Maternal and Umbilical Cord Plasma. Issue 6 (3rd May 2021) - Kuchan, Matthew J; DeMichele, Stephen J; Schimpf, Karen J; Chen, Xinhua
ABSTRACT: Background: α-Tocopherol (αT) is essential for fetal development. One study has shown that the human placenta preferentially transfers the natural stereoisomer, RRR -αT. But prenatal supplements generally contain synthetic αT (S-αT). Objectives: We aimed to determine if umbilical cord plasma is enriched for RRR -αT in racially diverse neonates from both uncomplicated and complicated pregnancies and if cord RRR -αT enrichment is impacted by maternal αT stereoisomer profile. Methods: We measured αT and αT stereoisomers in plasma from a randomly selected subset of 66 predominantly black and Hispanic maternal-fetal pairs from the Camden Study involving control ( n  = 28) and complicated pregnancies ( n  = 38). We collected maternal plasma at study entry (week 16 gestation; w16) and week 28 gestation (w28) and cord plasma at birth. Results: RRR -αT was the predominant stereoisomer in all maternal and cord plasma samples, but S-αT stereoisomers were found in most samples and comprised a high percentage of αT in some maternal-neonate pairs. Cord plasma had a higher percentage RRR -αT ( P  < 0.05) and lower percentage S-αT ( P  < 0.0001) than w28 plasma. Pregnancy status did not impact maternal or cord plasma concentrations of αT, RRR -αT, or S-αT; except plasma from complicated pregnancies was higher in S-αT at w28 than at w16 ( P  < 0.05). Maternal w28 αT did not correlate with cord αT. However, both maternal w28 αT and S-αT positively correlated with both cord S-αT ( r  = 0.340, P  = 0.0049; r  = 0.538, P  < 0.00001) and percentage S-αT ( r  = 0.399, P  = 0.001; r  = 0.786, P  < 0.00001) but negatively correlated with cord percentage RRR -αT ( r = −0.399, P  = 0.0009; r = −0.786, P  < 0.00001). Conclusions: The proportion of RRR -αT was higher in cord compared with maternal plasma in both uncomplicated and complicated pregnancies. Our data suggest that maternal S-αT raises cord S-αT and decreases the proportion of RRR -αT in the neonatal circulation. Because the bioactivities of RRR -αT and S-αT differ, this warrants future research to determine the importance of our observations to neonatal αT status. Abstract : Natural vitamin E (VE) was enriched in infant's blood at birth but may be displaced by synthetic VE derived from mother's diet. Natural VE is more bioactive than synthetic VE.